1991
DOI: 10.1136/ard.50.1.32
|View full text |Cite
|
Sign up to set email alerts
|

C reactive protein and immunoglobulin G in synovial fluid and serum in joint disease.

Abstract: C reactive protein (CRP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Thus, the bacterial receptor could effectively compete with its mammalian counterpart in vivo, even at low transferrin concentrations such as those probably existing on mucosal surfaces (42), and in other nonhematogenous gonococcal niches (39,49). In fact, this analysis indicated that the high-affinity binding site on the wild-type gonococcus was capable of binding transferrin with even higher affinity than its mammalian counterpart.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the bacterial receptor could effectively compete with its mammalian counterpart in vivo, even at low transferrin concentrations such as those probably existing on mucosal surfaces (42), and in other nonhematogenous gonococcal niches (39,49). In fact, this analysis indicated that the high-affinity binding site on the wild-type gonococcus was capable of binding transferrin with even higher affinity than its mammalian counterpart.…”
Section: Discussionmentioning
confidence: 91%
“…The above proteins, characterised by high affinity to TN [12,30,31], absorb it, leading to a drop in serum and SF TN proportional to inflammatory intensity. Fibrin-and cartilage-core-protein-bound TN anchor plasminogen and localise the fibrinolytic activity of the newly formed plasmin, contributing thus to pannus expansion, tissue remodelling, angiogenesis and cartilage destruction in RA.…”
Section: Discussionmentioning
confidence: 98%
“…Another important goal of this study was the assessment of SF TN in patients with arthritides characterised by diminishing inflammatory activity from RA to SSA and finally to OA patients. The concentration of any protein in SF depends on its concentration in serum, molecular weight and synovial membrane permeability, which in turn depends on the degree of the inflammatory process, as well as on the degree of its intra-articular production or consumption [30][31]. The significant positive correlation between serum and SF TN in patients with RA and SSA compared with OA patients could be explained by the increased permeability of the synovial barrier in inflammatory arthritides, with TN crossing the synovial membrane more easily.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, m-CPPD crystals are likely to encounter synovial fluid, which is an ultrafiltrate of plasma. The protein concentration of synovial fluid is low in the normal joint, but in inflammatory states increases with the influx of IgG, lipoproteins, fibrinogen, and albumin [14][15][16][17]. Adsorption of IgG and plasma proteins can potentially affect the degree of neutrophil inflammation induced by m-CPPD crystals.…”
Section: Discussionmentioning
confidence: 99%
“…In the inflamed joint, albumin, fibrinogen, lipoproteins, and immunoglobulins are able to migrate into the synovial fluid [13][14][15][16][17]. An abnormally high increase in the IgG concentration has been reported in the inflamed joint, indicating IgG production in the synovium [13][14][15]. These data indicate that crystals located in both the inflamed and noninflamed joints are likely to encounter large quantities of IgG relative to other plasma components.…”
Section: Introductionmentioning
confidence: 93%